Financial Education, Psychological And Spiritual On Financial Behavior - et. al., I Gusti Ayu Purnamawati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine financial education, locus of control (as psychological variable), and tri guna (as spirituality variable) on financial behavior. There are still many MSME actors who do not understand the importance of wise and precise financial management from recording to reporting. A questionnaire was used to collect data from 250 small and medium scale entrepreneurs in Bali Province. Multiple linear regression analysis is used to test financial behavior by analyzing financial education, locus of control, and spiritual variables. The results show that the variable financial education and locus of control have a positive and significant effect on financial behavior, while spirituality does no effect on financial behavior. The use of variables to determine financial behavior among MSME actors in this study is limited to three variables, namely financial education, locus of control, and spirituality. Also, respondents only addressed small and medium business owners so that they were less representative of other business people. This study adopts the Tri Guna concept. Tri Guna is the three characteristics that exist in humans with the satvam, rajas, and tamas parts. Humans can control these three uses, can balance the roles of the three so that whatever they do, including managing finances, will be managed wisely and with direction.